Social comorbidities? A qualitative study mapping syndemic theory onto gender-based violence and co-occurring social phenomena among Brazilian women - Casey D. Xavier Hall; Dabney P. Evans (BMC, 2020)
Abstract Background Gender-based violence is a globally recognized social problem impacting women and girls worldwide. Intimate partner violence (IPV) represents the most common form of gender-based violence. Among the countries grappling with gender-based violence is Brazil, which has identified high rates of IPV along with co-occurring social conditions such as adverse childhood experiences, community violence, and substance use. While the syndemic framework has incorporated IPV into understandings of HIV and other diseases, none have explicitly applied syndemic framework to understand IPV and co-occurring social conditions -- referred to here as "social comorbidities" -- in the absence of a biological outcome. This study aims to: (1) Examine perspectives on violence and relevant social comorbidities (substance use, community violence, and childhood abuse) among women living in Santo André, São Paulo State, Brazil; and (2) Apply the syndemic framework to a set of social comorbidities among women living in Santo André, São Paulo State, Brazil. Methods This thematic analysis applies a syndemic framework to 28 in-depth interviews with women in Santo André, Brazil. Interviews were recorded and transcribed verbatim in Portuguese. Our analysis examined themes relating to IPV, community violence, substance use, and other individual experiences and community issues using syndemics as an organizing framework (e.g. diseases, adverse interactions, disparity conditions, and enhanced disease transmission). Results Most participants described experiencing multiple social comorbidities including IPV, adverse childhood experiences, community violence, family violence, and substance use. Adverse interactions included increased financial conflicts, a sense of isolation, and increased severity of violence due to substance use. Long term enhanced "disease" progression included injury, increased mental health symptoms, femicide, and death. Conclusions Our results suggest that using a syndemic framework to understand IPV in the context of social comorbidities could be useful for understanding how these social phenomena may mutually reinforce each other and cause adverse interactions. Similar applications across other social phenomena may also be possible.